2019
DOI: 10.20870/oeno-one.2019.53.1.2293
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Sentinel-2 satellite images to monitor vine fields grown at a territorial scale

Abstract: Aim: The aim of this short note is to provide first insights into the ability of Sentinel-2 images to monitor vine growth across a whole season. It focuses on verifying the practical temporal resolution that can be reached with Sentinel-2 images, the main stages of Mediterranean vineyard development as well as potential relevant agronomic information that can be seen on the temporal vegetation curves arising from Sentinel-2 images.Methods and results: The study was carried out in 2017 in a production vineyard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 8 publications
2
26
0
1
Order By: Relevance
“…First, the border effect on S2 NDVI was evaluated in comparison to UAV NDVI pure. Even if some studies have already applied masks for border effects, a statistical justification is still missing (Devaux et al, 2019). In the second and third approaches, each block was analysed singularly (sub-field scale) and in relation to all other blocks (inter-field scale).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the border effect on S2 NDVI was evaluated in comparison to UAV NDVI pure. Even if some studies have already applied masks for border effects, a statistical justification is still missing (Devaux et al, 2019). In the second and third approaches, each block was analysed singularly (sub-field scale) and in relation to all other blocks (inter-field scale).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the potential of Sentinel-2 images in viticulture at a territorial scale to extract agronomic information and to quantify the impact of drought (Devaux et al, 2019;Cogato et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The pixel-spacing of 10 × 10 or 20 × 20 m implies the inclusion of both rows and inter-rows, affecting crop status evaluation [52]. This spatial resolution limits the employment of Sentinel-2 imagery to areas larger than 0.5 ha [26,33]. Moreover, the cloud coverage may represent a limitation to the usability of the images, especially during early spring, when weather conditions are unstable.…”
Section: Discussionmentioning
confidence: 99%
“…After correction, every spectral band image was cropped with an inner buffer of 10 m, creating a mask with QGIS 2.4 (http://www.qgis.org/). This step aimed to avoid the border effects [33]. In the case of CARI, which has a spatial resolution of 20 m, the cropping was done by selecting only the pixels entirely included in the same mask used for the 10 m spatial resolution VIs.…”
Section: Remote Sensing Datamentioning
confidence: 99%
“…(2) A great share of the study area (e.g., the south part of China, the north part of Iran, and Turkey) usually has the cloud cover mask problem. Although it can be addressed by the combination of several partially cloudy images, it leads to a remarkable increase of the satellite data number that must be acquired, stored, and processed (Devaux, Crestey, Leroux, & Tisseyre, 2019;Stillinger, Roberts, Collar, & Dozier, 2019). 3As there are many mountainous areas in the study area, it should be considered that even though the integration of optical and radar data can boost the separation among classes in low altitudes (e.g.…”
Section: Research Developments and Challenges In Sensorsmentioning
confidence: 99%